Style - Haynes, John, 1936- (London ; New York : Routledge, 1995)
Choosing le mot juste. Following and flouting conventions. Live and dead metaphors. Patterns of words in a text. Patterns of grammar in a text. The textual orchestration of patterns. The effects of the medium. Sequences of words and events. The selection of significant detail...
Keywords: English language; Style; English language -- Style -- Problems, exercises, etc